Enhancing adhesion and alignment of human gingival fibroblasts on dental implants. Issue 4 (April 2019) - Aktas, Oral Cenk; Metzger, Wolfgang; Haidar, Ayman; Açil, Yahya; Gülses, Aydin; Wiltfang, Jörg; Sacramento, Catharina Marques; Nothdurft, Frank Philipp
Abstract: Background: Promoting the directional attachment of gingiva to the dental implant leads to the formation of tight connective tissue which acts as a seal against the penetration of oral bacteria. Such a directional growth is mostly governed by the surface texture. Material and methods: In this study, three different methods, mechanical structuring, chemical etching and laser treatment, have been explored for their applicability in promoting cellular attachment and alignment of human primary gingival fibroblasts (HGFIBs). Results: The effectiveness of mechanical structuring was shown as a simple and a cost-effective method to create patterns to align HGIFIBs. Conclusion: Combining mechanical structuring with chemical etching enhanced both cellular attachment and the cellular alignment.